Popular dating apps in Indonesia and the United States - Ilmiawan, Ramadhani Akbar; Nafisah, Riza Maqfiratun; Nisa, Rizki Khoirun; Hart, Yaritza Haq Indra; Herdianto, Roni (Bulletin of Social Informatics Theory and Application, 2021)
The use of smartphones and the internet has changed the way people have partners. Location-based dating apps are also designed to maximize people's experience of finding partners. Apart from the various benefits, there are also risks such as adultery, fraud, and sexual crimes. In this research, we want to study the research and negative impacts of the three most popular dating apps in Indonesia and the United States. This research is a descriptive study with a qualitative narrative approach. The purpose of this study is to compare the use of dating apps in Indonesia and the United States and the negative impacts of these dating apps. This research finds that Tinder is the dating app with the most number of users and has the best privacy and security policy system in Indonesia and the United States. However, due to cultural and environmental differences in the two countries, internet crime is more prone to occur in the United States. Even so, the legal protection in the United States in resolving cases caused by dating apps is more robust than in Indonesia.